Does ESG performance promote total factor productivity? Evidence from China - Ma, Jiangming; Gao, Di; Sun, Jing (Frontiers in Ecology and Evolution, 2022)
Currently, environmental, social, and corporate governance (ESG) has become an all-pervasive term in the industrial sector, owing to its significant impact on corporate decision-making. While most of the studies provide evidence that the ESG significantly improves a firm's performance and value in the long run, few studies quantitatively analyzed the linkage between ESG and total factor productivity (TFP). Using the data of Chinese-listed companies during 2010–2020, we found that there is a positive relationship between ESG performance and TFP. ESG also improves the corporate TFP by reducing the financial constraints and improving the innovation input. Our extended analysis revealed that this beneficial effect tends to be stronger for SOEs (state-owned enterprises) and industries with high pollution levels. This study also brought to light some implications for Chinese firms in relation to their ESG practices and sustainable development.